2009
DOI: 10.1136/jnnp.2008.155895
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory impairment is more marked in patients with mild dementia with Lewy bodies than those with mild Alzheimer disease

Abstract: Simple bedside tests of olfactory identification merit further examination for their potential to improve the identification of patients with DLB when used alongside existing criteria. They are insufficiently specific for use in screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 27 publications
2
61
2
Order By: Relevance
“…Cross-sectional studies have clearly shown that hyposmia is a highly sensitive finding in PD, but it is not specific. Olfaction is also impaired in dementia with Lewy bodies (DLB) [11,12], pure autonomic failure [13], and amyotrophic lateral sclerosis, with mixed results found for Alzheimer's disease and multiple system atrophy [11,12]. Therefore, this nonmotor finding may be used as a premotor test to identify an at-risk group for PD, but it is certainly not diagnostic.…”
Section: Olfactionmentioning
confidence: 99%
“…Cross-sectional studies have clearly shown that hyposmia is a highly sensitive finding in PD, but it is not specific. Olfaction is also impaired in dementia with Lewy bodies (DLB) [11,12], pure autonomic failure [13], and amyotrophic lateral sclerosis, with mixed results found for Alzheimer's disease and multiple system atrophy [11,12]. Therefore, this nonmotor finding may be used as a premotor test to identify an at-risk group for PD, but it is certainly not diagnostic.…”
Section: Olfactionmentioning
confidence: 99%
“…In light of these observations, the American Academy of Neurology recommends the use of olfactory testing to differentiate PD from PSP and CBD, but not from MSA (McKinnon et al, 2007). It is noteworthy that olfactory impairment is not restricted to PD and MSA, but also occurs in Lewy body disease and Alzheimer's disease, old age, and as a side effect of the use of numerous medications (Liberini et al, 2000;Hawkes, 2003;Williams et al, 2009;Goldstein and Sewell, 2009). The possible role of Lewy body pathology in PD olfactory loss has been suggested (Braak et al, 2003;Morley and Duda, 2010).…”
Section: Early Anosmiamentioning
confidence: 99%
“…The recent development of a series of allosteric mGluR4 potentiators that display good pharmacokinetic properties, cross the blood-brain barrier, and have significant antiparkinsonian effects in various rodent models of PD provides a promising avenue toward the development of mGluR4-related therapeutic agents in PD (Niswender et al, 2008;Hopkins et al, 2009;Johnson et al, 2009;Williams et al, 2009;Niswender and Conn, 2010;Engers et al, 2011).…”
Section: Non-dopaminergic Therapiesmentioning
confidence: 99%
“…Mild cognitive impairment (MCI) can occur as a prodrome to parkinsonism (Dalrymple-Alford et al, 2010) or DLB (Williams et al, 2009). MCI in PD indicates a shorter time to dementia and represents a poor prognostic marker (Aarsland et al, 2009).…”
Section: Cognitive Impairmentmentioning
confidence: 99%